Catalytic defense against fungal pathogens using nanozymes - Qingzhi Wu (De Gruyter, 2021)
Fungal infections are still a major challenge for clinics, resulting from the resistance of drug-resistant fungi and the toxicity of antifungal drugs. Defense against fungal invasions via enzymatic catalysis has been found in nature. The use of nanozymes, as artificial enzyme mimics, may be a promising strategy to induce fungal death due to their advantages such as tunable catalytic activity, high stability, low cost, and easy preparation. Here, the importance of natural enzymes in the defense against fungi is outlined. The progress in antifungal performance and potential application of nanozymes and the related antifungal mechanisms are also summarized. Finally, the perspective and challenges in this field for future study, pointing out that nanozyme-based catalytic therapy represents a promising alternative strategy for antifungal treatment, are highlighted.